Quel genre de convictions dans les Conventions ? Esquisses d’auto-ethnographie des droits humains des femmes en tant qu’économies morales : le cas des Modifications Génitales Féminines - Michela Fusaschi (Archivio Antropologico Mediterraneo)
Based on ethnographic research on the so-called Female Genital Mutilations/FGM in Italy and in the health field, in this article the author, that adopts the term Modification/MoGf, has chosen two sketches of Self-Ethnography to criticize some international documents and, in particular, the Istanbul Convention on Gender-based Violence. Through an analysis of concepts such as culture, tradition, gender, victims and patriarchy, assumed in an antihistoric and essentialist key in these texts, the author highlights how they are the result of ‘convictions’ of a mainstream Western difference feminism and of an agreed-upon language which has helped foster human rights of women rhetoric as moral economies. Finally, the author wants to show how these same concepts have been incorporated and strategically performed by social actors to create a transnational moral subject rather than justice subject.